Models of antenatal classes for pregnant mothers - Sriatmi, Ayun; Suwitri, Sri; Shaluhiyah, Zahroh; Nugraheni, Sri Achadi (Universitas Muhammadiyah Purwokerto, 2022)
Introduction: Although it has proven to be helpful, the attendance of pregnant mothers in Antenatal Classes (AC) was still low, so an ineffective breakthrough application of AC was needed according to the mother's wishes and interests.Objective: The study aimed to compare various models of practical AC for pregnant mothers to improve behavior prevention of high-risk pregnancies.Method: This study is quasi-experimental with a nonequivalent control group and pre-posttest design. The population of all pregnant mothers in Semarang City, with 181 samples, was divided into three groups (Extended, Virtual and Conventional). Measurements were carried out four times to see the mean score increasing, and the results of the last measurement were analyzed using the One Way ANOVA test to compare the effectiveness of these three groups.Results: There was an increase in the mean value of all dimensions of the behavior of high-risk prevention based on its measurement stages. The extended model has the highest improvement, followed by the Virtual model. Statistically, there was a better chance in all behavioral dimensions after the intervention. There were differences in all dimensions of maternal behavior between the extended and the conventional model. In contrast, only knowledge and practice differed in the virtual model but not in attitudes, beliefs, and intentions.Conclusion: Extended and virtual models of AC effectively improved high-risk prevention behaviors better than conventional models. Although the increase was not as high as the extended model, the virtual model has an excellent opportunity to be developed as a strategy to overcome time constraints for mothers and health providers.